To jump or not to jump: Mule deer and white‐tailed deer fence crossing decisions - Emily N. Burkholder; Andrew F. Jakes; Paul F. Jones; Mark Hebblewhite; Chad J. Bishop (Wildlife Society Bulletin)
ABSTRACT Modified fencing structures have been recommended with the intention of enhancing ungulate movement. Ungulates such as mule deer (Odocoileus hemionus) and white‐tailed deer (O. virginianus) typically negotiate fences by jumping over them. We examined 2 fine‐scale fence crossing decisions to determine factors influencing 1) crossing success and 2) the mode of crossing by 2 sympatric deer species. From 2010 to 2016, we used remote cameras along fence lines in 2 study areas—Canadian Forces Base Suffield in southeastern Alberta, Canada, and The Nature Conservancy's Matador Ranch in north‐central Montana, USA—that captured images of deer–fence interactions before and after fence modifications were installed. We used logistic regression to model the probability of deer successfully crossing a fence and mode of crossing (jumping over vs. crawling under) based on fence characteristics and demographic factors. We documented 486 crossing attempts, of which 313 were successful (64.4%), indicating that pasture fences acted as a semipermeable barrier to deer. Of these 313 successful attempts, 152 crawled under the fence (48.6%) as opposed to jumping over it. We documented behavioral differences in mode of crossing between species when successfully crossing a fence. Results indicate that deer are selecting known crossing sites at broad scales as places to negotiate fences, and when assessing finer scale decisions at these sites, white‐tailed deer seemed to acclimate better than mule deer to our imposed changes (switched from crawling under to jumping over the fence). Though sample size was low in terms of use at modified fence sites, we recommend visually inconspicuous modifications (such as clips to increase the bottom wire height as opposed to goat‐bars) when implementing pasture fencing that was friendlier for deer. We also recommend modifications be implemented strategically; placement of modifications may be just as important to consider as the modification type. © 2018 The Wildlife Society.